(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
Astropark branch of the Institute of Astronomy and Geophysics of the Mongolian Academy of Sciences is a planetarium hall where celestial bodies and astronomical phenomena are visualized using Konica Minolta "MS-8" analog equipment and through halls with physical exhibits showing the historical events of the joint Mongolian-Soviet space flight and space exploration. It has already reached 10 years of age, making a significant contribution to the dissemination of astronomy and space science. Astropark at that time had more than 121,000 enthusiasts interested in the causes of astronomical phenomena and space f light distributed based on scientific results. In addition, in recent years, we have developed a portable planetarium projector and dome for more than 29,000 villagers and residents and the regularity of the constellations was introduced and promoted. The Аstropark industry has made a great contribution to increasing the number of astronomy and natural science enthusiasts. The gradual development of space science in Mongolia has become the basis for the establishment of a Space research center. The Space Research Center began its work to gradually develop space technology in the country, as well as spread science through the planetarium equipment with two laboratories: Space Technology Laboratory and Astropark. With the help of Konica Minolta’s analog planetary equipment "MS-8", we have been successfully spreading astronomy for 10 years and updating our equipment with fully digital solutions for planetary equipment from RSA Cosmos, a subsidiary of Konica Minolta Group, and SkyExplorer astronomy simulation software, which made it possible to simulate information about the sky, celestial bodies, and the space between planets and galaxies based on the research of scientists. This article provides an overview of the work of Astropark over the past 10 years, its progress, and future steps.